The effect of combined transcranial direct current stimulation and pneumatic compression as part of a comprehensive recovery strategy in professional male top-level soccer players - Gonçalves, D. S.; Moscaleski, L. A.; da Silva, G. M.; Morgans, R.; Okano, A. H.; Moreira, A. (The Journal of Strength and Conditioning Research, 2024)
This retrospective study aimed to examine the effect of transcranial direct current stimulation (tDCS) combined with lower limb pneumatic compression during the postmatch recovery period in top-level professional male soccer players' physiological and perceptual markers of recovery status. During the 2022 season (baseline), pneumatic compression was performed as part of the recovery strategy, applied the day after official match play and psychophysiological measurements (pain, sleep, perceived recovery, and creatine kinase [CK] sampling) were performed on the second day postmatch. During the 2023 season, the tDCS protocol was introduced, with its application being performed simultaneously (in conjunction) with pneumatic compression. Recovery sessions following 10 matches in the 2022 season and following 10 matches in the 2023 season were included in the analyses. Compared with 2022 (baseline; pneumatic compression isolated), the players perceived an increased recovery on the second day postmatch when tDCS was used in conjunction with the pneumatic compression (mean = 12%; p = 0.008) and rated improved sleep quality for the nights after applying tDCS combined with pneumatic compression (mean = 7.5%; p = 0.029). On the second day postmatch, a significant reduction was observed in muscle pain/soreness (mean = 64%; p < 0.0001) and the CK concentration decreased when baseline (pneumatic compression isolated) was compared with tDCS + pneumatic compression (mean = 76%; p = 0.001). In summary, combining pneumatic compression with tDCS may enhance the effects of both interventions, leading to greater overall improvements in recovery. Further research is warranted to confirm these findings and explore the underlying mechanisms in more detail.